Strategies for alternate item formats on the NCLEX-RN exam - Silvestri, Linda Anne.; Mojica, Yazmin (St. Louis, Mo. : Saunders/Elsevier, 2007)
This book provides you with the preparation you will need to correctly answer alternate item questions on the NCLEX-RN examination. Organized by client needs to mirror the actual examination a 75-queston comprehensive test. A companion CD-Rom includes all of the questions from the book plus questions with audio components.
"CD features questions with audio components!"--Cover.
Keywords: National Council Licensure Examination for Registered Nurses; Nursing; Nursing; Nursing -- United States